1999
DOI: 10.1046/j.1365-2389.1999.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of soil organic matter as affected by long‐term manurial treatment

Abstract: Summary The composition of soil organic matter (SOM) is influenced by land use and fertilization. We studied changes in the SOM in a long‐term field experiment on a sandy Podzoluvisol. The control plot and four combinations of manurial treatments of the experiment were selected: one with mineral fertilizer only and three combinations of organic manure with mineral fertilizer: cattle manure + NPK, cattle manure + PK and straw + NPK. The SOM was extracted by sodium pyrophosphate solution (pH = 10) and hot water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 13 publications
2
50
1
3
Order By: Relevance
“…Such decrease, according to the authors, occurred due to the priming effect of carbon, which is the carbon reduction in soil after the input of organic matter in the area. Ellerbrock et al (1999) did not find alteration in the total content of C in soil either. This could be explained by the low contents of manure dry matter or by the characteristics of the carbon from swine liquid manure, rich in polysaccharides, protein, lipids, and other compounds that are thought to be easily degraded.…”
Section: Seasonmentioning
confidence: 58%
“…Such decrease, according to the authors, occurred due to the priming effect of carbon, which is the carbon reduction in soil after the input of organic matter in the area. Ellerbrock et al (1999) did not find alteration in the total content of C in soil either. This could be explained by the low contents of manure dry matter or by the characteristics of the carbon from swine liquid manure, rich in polysaccharides, protein, lipids, and other compounds that are thought to be easily degraded.…”
Section: Seasonmentioning
confidence: 58%
“…These authors evaluated the properties of soil treated with 28 pig slurry applications in a four year period in an area from which most of the plant matter produced was removed to feed cattle. Similalry, Ellerbrock et al (1999) observed no alteration in the total soil C content in a 34 year application period. This behavior may be explained by the low dry matter content of manure or by the proper characteristics of the carbon-containing compounds of pig slurry, which, for being rich in polysaccharides, protein, lipids and other compounds (Dinel & Gregorich, 1995), are considered easily degradable.…”
Section: Resultsmentioning
confidence: 89%
“…Resultados obtidos neste trabalho corroboram com os obtidos por Ceretta et al (2003) os quais, trabalhando com aplicações de dejetos líquidos em pastagens, também não constataram aumento no teor de C orgânico no solo, após 48 meses de aplicações sucessivas. Ellerbrock et al (1999), também não encontraram alteração no conteúdo total de C no solo, o que poderia ser explicado pelos baixos teores de matéria seca dos dejetos ou pelas próprias características do C dos dejetos líquidos de suínos, A.…”
Section: Figura 4 Valores De Cálcio No Perfil Do Solo (A) E Em Funçãunclassified